Bioaugmentation with a propionate-degrading methanogenic culture to improve methane production from chicken manure. (February 2022) - Li, Ying; Wang, Changrui; Xu, Xinrui; Sun, Yongming; Xing, Tao
Graphical abstract: Highlights: Bioaugmentation can improve methane production with high-ammonia feedstocks. Propionate-degrading methanogenic cultures enhanced AD performance. Volumetric biogas production improved at various organic loading rates. Methanogenic culture bioaugmentation accelerated VFA degradation. Bioaugmentation reconstructed the microbial community in the digester. Abstract: Volatile fatty acid (VFA) accumulation caused by high ammonia concentrations is often encountered during the anaerobic digestion (AD) of ammonia-rich substrates. In this study, propionate-degrading methanogenic cultures were introduced to augment the semi-continuous AD of chicken manure under high ammonia levels. Introduction of a methanogenic culture enhanced the methane yield in the bioaugmented digester by 17–26% when the organic loading rate (OLR) was 2–4 g L -1 d -1 compared to that in the control. When the OLR was further increased from 4.0 L -1 d -1 to 5.0 g L -1 d -1, and bioaugmentation ceased, methane yield improved by 15–18% under a high total ammonia nitrogen level of 5.0–8.4 g NH4 + -N/L. Moreover, bioaugmentation reconstructed the methanogenic community in the digester, promoting the dominance of hydrogenotrophic Methanobacterium and slightly increasing the abundance of aceticlastic Methanothrix and the syntrophic propionate-oxidizing bacteria Syntrophobacter, which were the key contributors to the improved AD under high ammonia concentrations.